Dietary and Physical Activity Behaviors of New York City Children from Different Ethnic Minority Subgroups - Vangeepuram, N (2012)
OBJECTIVE: To examine racial/ethnic differences in diet and physical activity behaviors in ethnic minority New York City children. METHODS: Cross-sectional data from a community-based study of 486 6–8 year old children were used. Race/ethnicity was derived using caregiver report of child’s race and Hispanic ancestry. Dietary intake was obtained by 24-hour diet recalls using the Nutrition Data System for Research. Physical activity was assessed with pedometers and caregiver interviews. We compared diet and activity measures across racial/ethnic subgroups using Chi Square and ANOVA tests. Multivariate analyses adjusted for age, gender, BMI, and caregiver education (with breastfeeding history and total energy intake included in diet models). RESULTS: Participants (n=486) were categorized as Mexican (29.4%), Dominican (8.4%), Puerto Rican (20.6%), other/mixed Hispanic (14.0%) or non-Hispanic Black (27.6%). Obesity rates were lower in non-Hispanic Blacks (18%) than in Hispanics (31%). Mexicans had the lowest obesity prevalence among Hispanic subgroups (25%) and Dominicans had the highest (39%). There were differences in mean daily servings of food groups with Mexicans having healthier diets and Puerto Ricans and non-Hispanic Blacks having less healthy diets. Sedentary time was lower in Mexicans than in other groups in adjusted models. Examination of additional models including home language did not show significant differences in the estimates. CONCLUSION: Diet and activity behaviors varied across racial/ethnic subgroups. Specifically, Mexican children had healthier diets, the least amount of sedentary time and the lowest rates of obesity among the Hispanic subgroups examined. Targeted interventions in ethnic subgroups may be warranted to address specific behaviors.